2021
DOI: 10.38003/sv.70.2.18
|View full text |Cite
|
Sign up to set email alerts
|

The application of digital tools in listening to music in music culture education

Abstract: Listening to music is a dominant activity in the Music Culture teaching in which students develop critical thinking about aesthetic value of music. Teachers mostly use CDs and DVDs as important tools during the music listening activity despite the development of technology. On today’s classes we meet digitally literate students born in a completely digitalized world, which represents a great challenge for teachers. The students and the system expect a wide range of digital contents – audio tracks, videos, anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…In the current study, some of the findings that emerged in students' Kahoot learning experiences are remarkable. The positive codes of "fun", "intense participation", "interaction", "attractiveness" and "easy use" are in line with the findings of Gil et al's (2022) music education study, while the codes of "motivation" and "competitive environment" are in line with the findings of Škoro and Kir (2021) and Saraçoğlu and Kocabatmaz (2019). In addition to these results, it was observed that the emerged negative findings had a short-term effect.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, some of the findings that emerged in students' Kahoot learning experiences are remarkable. The positive codes of "fun", "intense participation", "interaction", "attractiveness" and "easy use" are in line with the findings of Gil et al's (2022) music education study, while the codes of "motivation" and "competitive environment" are in line with the findings of Škoro and Kir (2021) and Saraçoğlu and Kocabatmaz (2019). In addition to these results, it was observed that the emerged negative findings had a short-term effect.…”
Section: Discussionsupporting
confidence: 85%